Evaluating the economic fairways for hydrogen production in Australia. (22nd October 2021) - Walsh, Stuart D.C.; Easton, Laura; Weng, Zhehan; Wang, Changlong; Moloney, Joseph; Feitz, Andrew
Abstract: Assessments of hydrogen project viability typically focus on evaluating specific sites for development, or providing generic cost-estimates that are independent of location. In reality, the success of hydrogen projects will be intimately linked to the availability of local energy resources, access to key infrastructure and water supplies, and the distance to export ports and energy markets. In this paper, we present an economic model that incorporates assessments of these regional factors to identify areas of high economic potential for hydrogen production – the so-called "Economic Fairways" for such projects. In doing so, the model provides a tool that can be used to inform investors and policy makers on the available opportunities for hydrogen development and their infrastructure requirements. The model includes analysis of the regional economic potential for both blue and green hydrogen projects. It accounts for hydrogen production from renewable (wind and solar) sources, as well as non-renewable sources (steam-methane reformation and coal gasification) combined with carbon capture and storage. Results from case studies conducted with the tool are presented, illustrating the potential for hydrogen production across Australia. Highlights: We present a new model to map the economic fairways for hydrogen production. The model considers production costs, and resource and infrastructure availability. The model accounts for both green and blue methods of production. Results illustrating the potential for Australian hydrogen production are presented.